Bi‐level JOMP for DOA estimation in coprime array with off‐grid targets. Issue 21 (24th September 2019) - Jiang, Ying; He, Minghao; Tang, Yuwen; Han, Jun; Fan, Xikun
Abstract : The direction of arrival (DOA) estimation for off‐grid targets in the coprime array, which can extend degrees of freedom, is studied. Among existing research results, joint orthogonal matching pursuit (JOMP) has obvious advantages in complexity, but drawbacks in accuracy. Therefore, a bi‐level iterative algorithm is proposed to improve estimation performance of JOMP in this study. First, JOMP is executed to obtain the initial estimations of DOAs and mismatch parameters. Then, an iterative proximity searching is implemented to update target vectors to decline the residual further. After that, on the strength of results of the secondary iteration, the signal spectrum and mismatch parameters can be obtained through exploiting LS algorithm. Simulation results verify effectiveness of the proposed algorithm.